Three new species of the lacebug genus Tingiometra from Cretaceous Burmese amber (Hemiptera: Heteroptera: Tingidae: Tingiometrinae) - Golub, Viktor B.; Heiss, Ernst (Zootaxa, 2020)
Three new fossil species of the genus Tingiometra Heiss et al., 2015 (T. pankowskii sp. nov., T. secunda sp. nov., T. yuripopovi sp. nov.) of the family Tingidae (Hemiptera: Heteroptera: Tingidae: Tingiometrinae) from Cretaceous Burmese amber (northern Myanmar) are described and illustrated. Features of similarities and differences between the four known Tingiometra species are discussed and a key to species is provided.